2015
DOI: 10.1021/jo5026755
|View full text |Cite
|
Sign up to set email alerts
|

Tandem β-Elimination/Hetero-Michael Addition Rearrangement of an N-Alkylated Pyridinium Oxime to an O-Alkylated Pyridine Oxime Ether: An Experimental and Computational Study

Abstract: A novel OH(-)-promoted tandem reaction involving C(β)-N(+)(pyridinium) cleavage and ether C(β)-O(oxime) bond formation in aqueous media has been presented. The study fully elucidates the fascinating reaction behavior of N-benzoylethylpyridinium-4-oxime chloride in aqueous media under mild reaction conditions. The reaction journey begins with the exclusive β-elimination and formation of pyridine-4-oxime and phenyl vinyl ketone and ends with the formation of O-alkylated pyridine oxime ether. A combination of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…We manually placed dopamine 1 within the cluster, resulting in the initial stationary-point ( SP ) complexes (Figure 3 ). The system was modeled at the (CPCM)/M06–2X/6–311++G(2df,2pd)//(CPCM)/M06–2X/6–31+G(d) level of theory employing the M06–2X functional designed by Zhao and Truhlar to accurately reproduce thermodynamic and kinetic parameters (Zhao and Truhlar, 2008 , 2011 ; Bell and Head-Gordon, 2011 ; Cheong et al, 2011 ; Picek et al, 2015 ; Saftić et al, 2015 ), being particularly successful in treating non-bonding interactions. To account for the polarization effects caused by the rest of the enzyme, we included a conductor-like polarizable continuum model (CPCM) (Cossi et al, 2003 ) with a dielectric constant of ε = 4, taking the rest of the parameters for pure water, as employed in many studies by Siegbahn, Himo and their co-workers in elucidating the catalytic mechanism of a large variety of enzymes (Himo, 2006 ; Siegbahn and Borowski, 2006 ; Siegbahn and Himo, 2011 ).…”
Section: Mechanistic Studies Of Monoamine Oxidase By Quantum Mechanicmentioning
confidence: 99%
“…We manually placed dopamine 1 within the cluster, resulting in the initial stationary-point ( SP ) complexes (Figure 3 ). The system was modeled at the (CPCM)/M06–2X/6–311++G(2df,2pd)//(CPCM)/M06–2X/6–31+G(d) level of theory employing the M06–2X functional designed by Zhao and Truhlar to accurately reproduce thermodynamic and kinetic parameters (Zhao and Truhlar, 2008 , 2011 ; Bell and Head-Gordon, 2011 ; Cheong et al, 2011 ; Picek et al, 2015 ; Saftić et al, 2015 ), being particularly successful in treating non-bonding interactions. To account for the polarization effects caused by the rest of the enzyme, we included a conductor-like polarizable continuum model (CPCM) (Cossi et al, 2003 ) with a dielectric constant of ε = 4, taking the rest of the parameters for pure water, as employed in many studies by Siegbahn, Himo and their co-workers in elucidating the catalytic mechanism of a large variety of enzymes (Himo, 2006 ; Siegbahn and Borowski, 2006 ; Siegbahn and Himo, 2011 ).…”
Section: Mechanistic Studies Of Monoamine Oxidase By Quantum Mechanicmentioning
confidence: 99%
“…UV (MeOH): (2df,2pd)//(SMD)/M06-2X/6-31+G(d) models employed here, which turned out to be very accurate in estimating both pK a and reaction thermodynamic values in solution. [25] All of the transition state structures were verified to have the appropriate imaginary frequency, from which the corresponding reactants and products were determined using the Intrinsic Reaction Coordinate (IRC) procedure. [26] pK a values were calculated in a relative fashion using AH + B [27] for the N-H deprotonation in 5 and 7, N,N,NЈ,NЈ-tetramethylguanidine (pK a = 13.65) [27] for DBUH + and pyridineH + , H 3 PO 4 (pK a = 8.48) [28] and H 2 PO 4 -(pK a = 10.58) [28] for the first and second deprotonation of H 2 CO 3 , respectively.…”
Section: -(1-mentioning
confidence: 99%
“…The ability of oximes to act as esterolytic agents had already been recognized in the late 1950s and various terms like oximolysis, esterolysis, thiocholine ester hydrolysis and cholinesterase pseudo-activity have been adopted to describe the phenomenon [2][3][4][5][6][7][8][9][10]. This reflects their biological role, making them especially effective reagents involved in the reactivation of acetylcholinesterase (AcChE) initially inhibited by organophosphorus poisons (pesticides, nerve gases) [1] or catalysts, which mimic the catalytic mode of hydrolases, as well as excellent Michael donors in nucleophilic additions [11]. The biological importance and pharmacological application of pyridinuim oximes arises from their abilities to reactivate AcChE, the essential enzyme involved in neurotransmission, inhibited by organophosphorus poisons.…”
Section: Introductionmentioning
confidence: 99%
“…AcCh + is more susceptible to neutral and base-catalyzed hydrolysis than ethyl acetate but less susceptible to acid-catalyzed hydrolysis [8], while majority of thioesters undergoes both acid and base-catalyzed hydrolysis [10]. Kinetic studies indicated that there are two distinct types of thioesters-one which possesses an activated carbonyl group due to the presence of electron-withdrawing substituents on the α-carbon and second type which lacks an activated carbonyl-unactivated thioesters such as AcSCh + [11]. Unactivated thioesters display three distinct regions in the pH-rate profile-HO − -ion catalysis above pH 7, neutral (uncatalyzed) hydrolysis between pH 2-7 and H + -ion catalysis below pH 2 [11].…”
Section: Introductionmentioning
confidence: 99%